2003
DOI: 10.1046/j.1365-2672.2003.01869.x
|View full text |Cite
|
Sign up to set email alerts
|

Modelling and optimization of inactivation of Lactobacillus plantarum by pulsed electric field treatment

Abstract: Aims: The effect of critical pulsed electric field (PEF) process parameters, such as electric field strength, pulse length and number of pulses, on inactivation of Lactobacillus plantarum was investigated. Methods and Results: Experiments were performed in a pH 4Á5 sodium phosphate buffer having a conductivity of 0Á1 S m À1 , using a laboratory-scale continuous PEF apparatus with a co-linear treatment chamber. An inactivation model was developed as a function of field strength, pulse length and number of pulse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
66
0
3

Year Published

2008
2008
2020
2020

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 75 publications
(76 citation statements)
references
References 23 publications
7
66
0
3
Order By: Relevance
“…Recently many non-thermal preservation technologies have been proposed. Among all emerging non-thermal technologies, high intensity PEF processes the food without compromising on taste and flavor (Lado and Yousef 2002;Abram et al 2003). For example, the PEF treatment to carrot juice assured insignificant diminution in pH, electric conductivity, color, brix and titratable acidity along with log reduction of 4.3 and 3.4 D for mold and yeast respectively while keeping the mineral element persevered (Akin and Evrendilek 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Recently many non-thermal preservation technologies have been proposed. Among all emerging non-thermal technologies, high intensity PEF processes the food without compromising on taste and flavor (Lado and Yousef 2002;Abram et al 2003). For example, the PEF treatment to carrot juice assured insignificant diminution in pH, electric conductivity, color, brix and titratable acidity along with log reduction of 4.3 and 3.4 D for mold and yeast respectively while keeping the mineral element persevered (Akin and Evrendilek 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, some authors concluded that applying the same quantity of energy, the inactivation achieved was greater at higher pulse width. increased the pulse duration from 2 to 4 μs for the same treatment time, they found that the inactivation was greater with 4 μs but the differences were greater at high electric field intensities and Abram et al, (2003) also found that when they increased the pulse width over 1 μs, with E=25 kV/cm and the same energy input, the inactivation increased with the pulse width. The effect of pulse width is not clear and seems to vary depending on the conditions applied such as electric field.…”
Section: Raso Et Al (2000) and Mañas Et Al (2001) Also Found Thatmentioning
confidence: 91%
“…However, several studies conclude that a pulse width increase produces higher microbial inactivation Abram et al, 2003Abram et al, , Élez et al, 2005, but only under low field intensities (25-28 kV/cm). In the enzyme inactivation by PEF, Giner et al, (2001) and Élez et al, (2006 b) observed a greater POD and PPO inactivation by increasing pulse width.…”
Section: Pulse Width (W)mentioning
confidence: 99%
See 2 more Smart Citations